Industrial deepening in Malaysia: policy lessons for developing countries - Tham, Siew-Yean; Loke, Wai Heng (Massachusetts Institute of Technology Press, 2011)
The Malaysian economy has undergone substantial industrial transformation, shifting from primary commodity production to manufacturing in slightly more than 5 decades since achieving independence. However, efforts to deepen manufacturing development have not succeeded in nurturing a critical mass of domestic entrepreneurs with indigenous innovative capacities as industrialization continues to be dependent on imported technology and capital. Instead, the manufacturing sector is facing premature deindustrialization. In view of these developments, this study aims to assess the extent of industrial deepening in a country through the development of linkages, as well as the key factors that have contributed to this. This has important policy lessons for other developing countries that are following similar export-oriented, foreign direct investment-led strategies for their industrial development. The main findings of this study indicate that while trade and investment policies have contributed to the development of the manufacturing sector, they have also fostered closer integration with the rest of the world rather than within the domestic economy. The electrical and electronics subsector has relatively weaker backward linkages than other subsectors in the economy. Deepening internal integration requires complementary labor, human capital, and technology policies that can facilitate the development of linkages in the manufacturing sector.